Small Non-coding RNA in Plants: From Basic Science to Innovative Applications - Tarquini, Giulia; Cione, Erika (MicroRNA, 2023)
Plants possess an arsenal of different classes of small RNAs (sRNAs) of variable size, which play a regulatory role in a multitude of physiological and pathological processes via transcriptional or post-transcriptional gene silencing. The hard challenges that agriculture will face in the next few decades, such as an increasing demand for agrifood production related to the global increase in population, have stimulated the development of innovative biotechnological approaches in agriculture. In this regard, the use of artificial sRNAs has already been exploited successfully for many purposes, including control of severe plant diseases, improvement of genetic and agronomic traits of cultivated species, and increasing the nutritional value of plant foodstuffs. This strategy relies on the application of synthetic sRNA molecules to induce specific physiological responses by triggering appropriate RNA silencing pathways. This review contextualizes the use of artificial sRNAs in consideration of the huge diversity of RNA silencing mechanisms in plants. Additionally, the discussion also examines microRNAs from edible plants and exosome-like vesicles, also known as plant-derived edible nanoparticles (ENPs), which themselves can act as micronutrients.
Keywords: PTGS